Rudolf J. Kordon: in memory of the chief custodian of VIR’s seed collection during the Great Patriotic War - A. V. Shlyavas (Труды по прикладной ботанике, генетике и селекции, 2025)
The name of Rudolf J. Kordon (1884–1961) is usually associated with the siege period of the All-Union Institute of Plant Industry (currently the N.I. Vavilov All-Russian Institute of Plant Genetic Resources, VIR). Rudolf Kordon was among those who saved the Institute’s seed collection in the besieged city. However, the life of this scientist remains little known to the public. For more than thirty years, R. Kordon worked with the Fruit Crop Department of VIR, was the author and coauthor of 12 apple cultivars, and developed recommendations for apple-tree cultivation under the conditions of the Crimea and the Northwest of Russia, which have not lost their value to this day.